Septic arthritis following mumps in a case of steroid dependent nephrotic syndrome: a case report - Bhoomraddi, Karan J.; Koshatwar, Vaishnavi G.; Inamdar, Prithi; Rai, Rajesh K.; Naulakha, Ravi P. (International Journal of Contemporary Pediatrics, 2024)
Nephrotic syndrome is a common renal disorder with an incidence of 20 to 40 per million population in developed countries. Children with nephrotic syndrome are especially susceptible to infections such as cellulitis, spontaneous bacterial peritonitis, and bacteremia. However, septic arthritis is an extremely rare complication in nephrotic syndrome. A 6-year-old girl with steroid dependent nephrotic syndrome relapsed following mumps parotitis and developed swelling of the right knee with restricted movements. Ultrasonography (USG) and magnetic resonance imaging (MRI) were suggestive of septic arthritis. The child responded to intravenous Vancomycin and Ceftazidime. We present a rare complication of nephrotic syndrome as septic arthritis, previously reported only once.